Tax Avoidance Planning through CoreTax: Strategic Analysis and Its Impact on Tax Compliance and Fiscal Sustainability - Hartono, Hartono (Jurnal Multidisiplin Sahombu, 2025)
This study explores how CoreTax, a digital tax planning platform, is utilized by companies in Indonesia to implement legal yet aggressive tax avoidance strategies. Using a qualitative case study approach, data were collected through interviews with tax practitioners, analysis of corporate tax documents, and simulations of tax scenarios. The findings reveal that CoreTax enables the identification of tax-saving opportunities through features such as tax gap analysis and simulated transfer pricing, allowing companies to reduce their effective tax rates. While these strategies are legally permissible, they raise concerns about fairness, fiscal sustainability, and regulatory oversight. The study highlights the dual nature of tax technology, promoting efficiency on one hand while enabling regulatory circumvention on the other. It recommends that tax authorities strengthen digital audit capacity and update anti-avoidance regulations to address technology-based planning. By offering a contextual understanding of tax technology usage, this study contributes to policy discussions on digital taxation and corporate compliance behavior.